Excavating the social representations and perceived barriers of organ donation in China over the past decade: A hybrid text analysis approach - Zhang, Zizhong; Jin, Jing; Luo, Chen; Chen, Anfan (Frontiers in Public Health, 2022)
Background Organ donation has been claimed as a prosocial behavior to prolong the recipient's life and deliver great love. However, the supply-demand ratio of organs in China is highly unbalanced. Being entangled with multiple factors derived from individual and supra-individual levels, organ donation in China is important but sensitive. Previous scholars usually depended on obtrusive approaches to explore the facilitators and hindrances of organ donation, which is hard to discover genuine perceptions toward organ donation. Besides, relatively limited scholarly attention has been paid to what hampers organ donation in China. Objective We intended to excavate the diversified social representations and perceived barriers to organ donation in China over the past decade. Method Two kinds of text analysis methods—semantic network analysis and conventional content analysis, were applied to 120,172 posts from ordinary users on the Sina Weibo platform to address the research questions. Results Regarding social representations, the “hope, understanding, and acceptance” of organ donation was the most pronounced one (34% of the whole semantic network), followed by “family story” (26%), “the procedure of organ donation in NGOs” (15%), “the practical value of organ donation” (14%), and “organ donation in the medical context” (11%). Regarding perceived barriers, a four-layer framework was constructed, including (1) the individual level, mainly about the fear of death and postmortem autopsy; (2) the familial level, which refers to the opposition from family members; (3) the societal level, which alludes to distrust toward medical institutions and the general society; (4) the cultural level, which covers religious-cultural concerns about fatalism. Conclusion In concordance with prior works on social representations regarding organ donation, the current study also uncovered the coexistence of antithetical representations about organ donation—the longing for survival and the fear of death. This representation pair serves as the foundation of Chinese people's ambivalence. Besides, family-related narratives were dispersed over various representations, demonstrating the critical position of family support in organ donation. Moreover, the four-layer framework concerning donation barriers affords a reference for future empirical studies. The practical implications of this work are further discussed.